Local pH-dependent conformational changes leading to proteolytic susceptibility of cystatin C. - Berti, P J (1994)
Cystatin C, a cysteine protease inhibitor, was subject to hydrolysis at two sites when complexed with papain and in the presence of excess papain. A pH-dependent cleavage at His-86 increases Asp-87 was observed, as well as a pH-independent one at Gly-4 increases Lys-5. His-86 increases Asp-87 hydrolysis increased with decreasing pH and was characterized kinetically. It could be described by a single ionization with pKa = 3.4 +/- 0.2 and (kcat./Km)max. = 1.4 (+/- 0.4) x 10(4) M-1.s-1 at I = 0.3 M. C.d. spectroscopy, also at I = 0.3 M, demonstrated a conformational change with pKa = 3.2 +/- 0.2, indicating that the pH-dependence of hydrolysis was due to a conformational change in cystatin C. At I = 0.15 M, the pKa of the conformational change observed by c.d. shifted to 4.1 +/- 0.1. This indicates that at physiological ionic strength of 0.15 M, a significant proportion of cystatin C complexed with protease would be in a proteolytically labile conformation over the pH range 4.5 to 5, which is encountered in lysosomes. This may constitute a mechanism for clearing inappropriately localized cystatins. A pH-dependent conformational variability in this region of the inhibitor could explain the differences in the X-ray crystallographic and n.m.r. structures of the homologous chicken cystatin. The ionic-strength dependence of ionization indicates a hydrophobic stabilization of the ionizable group. The lack of pH-dependence of hydrolysis at Gly-4 increases Lys-5, with kcat./Km = 220 +/- 41 M-1.s-1 in the pH range 3.89 to 7.96 was unexpected in light of the normal, bell-shaped pH-dependence of papain-catalysed hydrolyses. This may reflect a different rate-limiting step of cystatin C hydrolysis.